Assessment of Correlation Between p16INK4a Staining, Specific Subtype of Human Papillomavirus, and Progression of LSIL/CIN1 Lesions: First Comparative Study. (1st July 2014) - Razmpoosh, Maryam; Sansregret, Andrée; Oligny, Luc L.; Patey, Natalie; Dormoy-Raclet, Virginie; Ducruet, Thierry; Bouron-Dal Soglio, Dorothée
Abstract: Objectives: To study and compare the effectiveness of p16 INK4a staining and specific human papillomavirus (HPV) subtypes as a prognostic marker in cervical intraepithelial neoplasia grade 1 (CIN1; low-grade squamous intraepithelial lesions). Methods: Sixty-four cervical samples diagnosed as CIN1 and stained with p16 INK4a, with HPV status assessed by polymerase chain reaction–direct sequencing. Results: Of the 34 p16 INK4a -negative biopsy specimens, 26 regressed, seven persisted, and one progressed. Of the 20 p16 INK4a diffusely positive biopsy specimens, seven regressed, eight persisted, and five progressed. Ten biopsy specimens stained positive only in the lower one-third of the sample, of which seven regressed and three persisted. p16 INK4a diffusely positive CIN1 lesions were associated with only high-risk HPV subtypes, with the exception of one HPV-negative biopsy specimen. Three different high-risk HPV subtypes and one low-risk HPV subtype (HPV66) were identified in the six CIN1 lesions that progressed. Conclusions: There is a significant relationship between p16 INK4a immunostaining and follow-up ( P = .002). p16 INK4a -negative specimens or positivity in the lower one-third of CIN1 lesions seldom progress to a CIN2-3 lesion.